SINERGISITAS ANTAR OPD DALAM PENANGANAN ANGKA PERNIKAHAN DINI DI KABUPATEN BOJONEGORO - Fatimmatul Munawaroh; Ahmad Taufiq; Junadi Junadi (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the synergy of Regional Government Organizations (OPD) in reducing early marriage. This research uses descriptive qualitative research methods and data collection techniques using field studies which are carried out directly at the research location through observation, interviews and documentation. This research uses the concept of Najiyati and Rahmat (2011), Synergy can be built in two ways, namely Communication and Coordination. The results of the research show that synergy between Regional Government Organizations (OPD) in handling the number of early marriages in Bojonegoro Regency has made various efforts but the results are not yet optimal. It can be seen: 1) So far they have carried out good synergy, they have carried out socialization between Regional Government Organizations (OPD ) also invited parents and teenagers who are still underage. 2) create a joint program to reduce the rate of early marriage.